The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1161/circulationaha.121.055018
|View full text |Cite|
|
Sign up to set email alerts
|

Atrial Fibrillation and Dementia: A Report From the AF-SCREEN International Collaboration

Abstract: Growing evidence suggests a consistent association between atrial fibrillation (AF) and cognitive impairment and dementia that is independent of clinical stroke. This report from the AF-SCREEN International Collaboration summarizes the evidence linking AF to cognitive impairment and dementia. It provides guidance on the investigation and management of dementia in patients with AF on the basis of best available evidence. The document also addresses suspected pathophysiologic mechanisms and identifies knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
3
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(115 citation statements)
references
References 105 publications
(158 reference statements)
7
96
3
9
Order By: Relevance
“…The present analysis, despite using general terms to maximize sensitivity, retrieved a low number of studies. In fact, the AF-SCREEN International Collaboration has recently [ 14 ] highlighted the urge for dedicated research to establish the role of AF treatment strategies in preventing dementia. The effect of sinus rhythm maintenance has been investigated especially in regard to hard clinical endpoints, whereas evidence on cognitive impairment is limited and burdened by heterogeneity in the scale adopted to measure cognitive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present analysis, despite using general terms to maximize sensitivity, retrieved a low number of studies. In fact, the AF-SCREEN International Collaboration has recently [ 14 ] highlighted the urge for dedicated research to establish the role of AF treatment strategies in preventing dementia. The effect of sinus rhythm maintenance has been investigated especially in regard to hard clinical endpoints, whereas evidence on cognitive impairment is limited and burdened by heterogeneity in the scale adopted to measure cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Among the possible therapeutic strategies for AF management, catheter ablation (AFCA) is the most effective in achieving rhythm control and improving quality of life [ 11 , 12 , 13 ]. Lately, the possible role of rhythm control strategies in preventing cognitive decline has been investigated [ 14 , 15 , 16 , 17 , 18 , 19 ]; however, the effect of AFCA on dementia occurrence, a highly relevant medical and socio-economical event, has rarely been studied and remains matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…While there is still limited supporting evidence for systematic screening for AF, as well as associated cost implications [26], targeted screening, systemic opportunistic screening or smartphone algorithms, may be a more cost-effective option when using AI-enhanced ECG systems. With an increasing consumer adoption of wearable healthcare technologies [27,28], the incorporation of AIenhanced algorithms for AF screening [29][30][31][32] would be expected to AF-related morbidities in the long-term [33,34].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…However, other studies have reported that the AF-related risk of dementia can be explained by brain infarcts, with the majority of infarcts being silent ( Sposato et al, 2017 ; Kühne et al, 2022 ). AF and dementia share multiple risk factors, and while many studies adjust for these risk factors at baseline, they have short follow-up times and are not always reassessed ( Rivard et al, 2022 ). Further, subclinical AF could be a confounding cause of dementia in patients with AC.…”
Section: Pathophysiology Of Atrial Cardiopathy-related Cognitive Impa...mentioning
confidence: 99%